ANALISIS KEPUTUSAN KUBA DALAM NORMALISASI HUBUNGAN DIPLOMATIK DENGAN AMERIKA SERIKAT TAHUN 2008-2015 - Asri Yudiari, Luh Gede Ervina; Kumala Dewi, Putu Ratih; Prameswari, A.A. Ayu Intan (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2020)
ABSTRACT The diplomatic relations between Cuba and the United States (US), which had been interrupted for decades, were reestablished when the US government took a stand to embrace Cuba and try to build cooperation. Cuba has been imposed sanctions of economic embargo by the US which led to a drastic decline in the Cuban economy and try to isolate Cuba from international relations. For half a century Cuba has tried to withstand the effects of these sanctions. Normalizing diplomatic relations is a hope for Cuba to minimize sanctions imposed by the US. US give a hope to reestablish the diplomatic relation, and Cuba had to choose, remain in the status-quo or normalize diplomatic relation with US.This research describe Cuba decision and see through environmental and domestic factors influeces the policy. Keywords: Cuba and United States, Diplomatic Relations, Foreign Policy, Normalization.